RESULTS OF AN OPEN-LABEL COMPARATIVE RANDOMIZED CLINICAL TRIAL OF AXOGLATIRAN® FS (F-SINTEZ, RUSSIA) EFFICIENCY AND SAFETY IN COMPARISON WITH COPAXONE®-TEVA (TEVA PHARMACEUTICAL INDUSTRIES LTD., ISRAEL) IN PATIENTS WITH RELAPSING-REMITTING MULTIPLE SCLEROSIS - F. A. Khabirov; T. I. Khaibullin; E. V. Granatov; N. N. Babicheva; L. A. Aver’yanova; S. R. Shakirzyanova (Нервно-мышечные болезни, 2017)
Objective. Comparison of Axoglatiran® FS (F-Sintez,  Russia) and Copaxone®-Teva (Teva Pharmaceutical Industries Ltd.,  Israel) efficiency and safety in patients with relapsing-remitting multiple sclerosis. Materials and methods. In the study 150 patients with relapsing-remitting multiple sclerosis were randomized into 2 groups: patients in the 1st group (n = 100) received treatment with Axoglatiran® FS, patients in the 2nd group (n = 50) received treatment with Copaxone®-Teva. Vital signs of every patient in the study were monitored accompanied by physical examinations, neurological examinations with EDSS (Expanded Disability Status Scale) and MSFC (Multiple Sclerosis Functional Composite) evaluations, magnetic resonance imaging of the brain and lab tests. Results. Mean age (M ± SD) of the patients in the 1st group was 32.8 ± 8.7 years (20–54  years), percentages of men and women were 34 and 66 % respectively, mean age of multiple sclerosis onset was 27.93 ± 7.72 years (11–48 years). Median (Me), lower and upper quartiles estimates [LQ; UQ] on the EDSS scale were 2 [1.5; 3.0] steps (1.0–4.5  steps). In the 2nd group mean age of the patients was 35.2 ± 9.5 years (18–57  years), percentages of men and women were 24 and 76 % respectively, mean age of multiple sclerosis onset was 26.5 ± 6.9 years (18–47  years), EDSS estimates were 2.25 [1.5; 3.5] steps (1–5  steps). In the 1st group 88 (88 %) patients completed the study, in the 2nd  group 44 (88 %) patients completed the study. Among them in 73 (82.95 %) patients in the 1st group and 34 (77.27 %) patients in the 2nd  group the disease didn’t exacerbate (p > 0.05). In both groups no progression according to the EDSS and MSFC scale was observed (p > 0.05). Magnetic resonance imaging data showed that dynamics of the total number of T2 lesions, contrast-enhancing T1 lesions, atrophy degree estimated using internuclear index were comparable in both groups (p > 0.05). Safety profiles of Axoglatiran® FS and Copaxone®Teva were evaluated as satisfactory in both groups: local reactions were the most common adverse event (57.7 and 63.0 % in the 1st  and 2nd groups respectively).Conclusion. Efficiency, safety and tolerability of Axoglatiran® FS is comparable with the reference medicine Copaxone®-Teva in patients with relapsing-remitting multiple sclerosis. This result allows to recommend the use of Axoglatiran® FS in clinical practice.